Arthur, Chris. Words of the Grey Wind – Family and Epiphany in Ulster - Lavalle, Luci Collin (ABEI Journal, 2009)
Arthur, Chris. Words of the Grey Wind – Family and Epiphany in Ulster. Belfast: Blackstaff Press, 2009. pp. 253. ISBN 978-0-85640-843-4